Ejection Fraction Decline and Cardiotoxicity Following Anthracycline Chemotherapy: A Risk-Focused Study from an Indonesian Tertiary Care Center - Rizkyastari Onny; Tutik Harjianti; Pendrik Tandean; Syakib Bakri; Himawan Sanusi; Andi Alfian Zainuddin (Український журнал серцево-судинної хірургії)
Background. Anthracycline chemotherapy is a cornerstone of cancer treatment but poses a risk of cardiotoxicity, often presenting as cancer therapy–related cardiac dysfunction (CTRCD). Monitoring left ventricular ejection fraction (LVEF) is essential to detect early cardiac impairment and support safer treatment strategies.